1978
DOI: 10.1111/j.1467-6494.1978.tb01017.x
|View full text |Cite
|
Sign up to set email alerts
|

Personality and the location of identity1

Abstract: It was hypothesized that individuals vary in their general environmental orientation: some are oriented to the internal and some to the extemal environment. We next predicted that this'-difEMence would be reflected in the location of those characteristics by which such persons define their identity. A sample of 150 persons judged the location of a set of 22 identity^ chafactensfics. TEesecKarkctieristics were rated on importance for self and then correlated with personality tests assumed to assess individual d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
37
0
3

Year Published

1982
1982
2016
2016

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 64 publications
(42 citation statements)
references
References 9 publications
2
37
0
3
Order By: Relevance
“…While recognizing individual differences in terms of importance of possessions for personal identity (e.g., Sampson, 1978), Prelinger (1959 provided support for the proposed relationship between self and control over objects. Specifically, he found that objects over which the respondent had control, could manipulate, or objects by which she/he could be affected, were more likely to be perceived as parts of the self than objects for which neither was the case.…”
Section: Controlling the Ownership Targetmentioning
confidence: 99%
“…While recognizing individual differences in terms of importance of possessions for personal identity (e.g., Sampson, 1978), Prelinger (1959 provided support for the proposed relationship between self and control over objects. Specifically, he found that objects over which the respondent had control, could manipulate, or objects by which she/he could be affected, were more likely to be perceived as parts of the self than objects for which neither was the case.…”
Section: Controlling the Ownership Targetmentioning
confidence: 99%
“…As an extension of this, Friedman adopted the position of a psychological cartographer and advanced a two-dimensional model of self-concept expansiveness which permits the understanding of the self-concept in terms of its boundaries in demarcating aspects of the Self that are, and are not, experienced by the individuals as components of their personal identities. The dimensions themselves are a combination of Sampson's (1978) notion of identity spatiality (i.e., locus of identity in space) and Shostrom's (1963) concept of temporality of self-concept (i.e., the degree of present-centeredness versus past or future orientedness of identity). In essence, Friedman created a two dimensional framework that can be used to map the self-concept onto the Self.…”
Section: Transpersonal Approaches To Spiritual Identitymentioning
confidence: 99%
“…To facilitate self-verification, individuals establish and maintain self-verification contexts. Identity theorists suggest that individuals play an active role in confirming their identity (Burke & Stets, 1999, 2009Leary, Wheeler, & Jenkins, 1986;Sampson, 1978;Snyder, 1981;Stryker & Burke, 2000;Swann, 1987;Swann & Hill, 1982;Swann, Pelham, & Krull, 1989;Swann & Read, 1981). People alter or create contexts in which their identity can be affirmed more often and maintain these contexts once they have been established (Burke & Stets, 1999, 2009Stryker & Burke, 2000).…”
mentioning
confidence: 99%